Entrepreneurship and social networks in IT sectors: the case of the software industry in Portugal - Salavisa, I.; Videira, P.; Santos, F. (Journal of Innovation Economics & Management, 2009)
The research presented in this paper aims to clarify the role played by entrepreneurs’ social networks in knowledge-intensive industries through the creation and early growth of companies in IT sectors. In this paper we will focus on the software sector, and more specifically on the companies that produce software for telecommunications. Since large software houses are diversified, we have extended our study to the entire sector, excluding multinational companies.